The Impact Of Peer Teaching On Eleventh-Grade Students’ Ability To Write Descriptive Texts At Smk 1 Tamansiswa Pematangsiantar - Tiondina Samosir; Selviana Napitupulu (Journal Innovative Practices in Education (JIPE), 2026)
Writing is one of the essential skills in English learning, yet many vocational high school students still struggle to express their ideas coherently and grammatically. Peer teaching strategy has been widely recognized as an effective approach to enhance students’ language skills through collaborative learning, but limited studies have investigated its impact on writing descriptive texts in the vocational school context. Therefore, this study aimed to determine the effect of the peer teaching strategy on students’ ability to write descriptive texts at SMK 1 Tamansiswa Pematangsiantar. The study employed a pre-experimental design with a pre-test and post-test administered to one class of students which is XI MPLB 2. The findings revealed a substantial improvement in students’ writing performance, where the mean score increased from 56.4 in the pre-test to 79.8 in the post-test. The result of the paired sample t-test showed a significant difference between the two means with a p-value of 0.000 < 0.05, indicating that the peer teaching strategy had a significant effect on students’ writing achievement. In conclusion, peer teaching effectively improved students’ writing ability in descriptive texts by fostering cooperation, confidence, and peer feedback